Clinical bioethics. Surgical approach to an intravenous drug addict with diagnosis of endocarditis - Manna, Raffaele; Cascio, Marietta; Spagnolo, Antonio G. (Medicina e Morale, 1990)
The authors deal with a case study of a 37 year old man with a history of intravenous drug use, admitted to the hospital with a diagnosis of endocarditis requiring cardiac surgery for valve replacement. The cardiac surgery consultation team is in doubt as to wath to do because surgical risks and the likelihood of recidivism would be high, but above ali because operative and postoperative care would be costly and the patient is poor and inadequately insured. In examining the clinical data and the values involved in the case, the authors conclude that cardiac valve replacement is the only therapeutic possibility for the patient and that clinical decision-making should not be based on a patient's payer status. Various positions in the field of ethics, economics and allocation of scarce resources are also discussed.